Knowledge and perception regarding the prevention of traffic noise pollution among students of North Karnataka - N., Bhoomika; Yadavannavar, M. C.; Pattankar, Tanuja P.; Doddihal, Chandrika; Sorganavi, Vijaya (International Journal Of Community Medicine And Public Health, 2024)
Background: Noise pollution is an insidious and underestimated environmental threat, that poses diverse health risks such as sleep disturbances, cardiovascular ailments, impaired work and academic performance, hearing impairments, and mental health issues. Understanding student’s awareness, perspectives, and attitudes toward traffic noise pollution and its health impacts is crucial. Objective was to evaluate the knowledge and perceptions of students towards traffic noise pollution. Methods: The present study was conducted in Vijayapura during August and September 2023, this cross-sectional study involved 304 students. A self-administered questionnaire was used to assess the existing knowledge and perceptions regarding traffic noise pollution prevention among students of north Karnataka. Results: Among 304 studied participants, 56.3% were females and 43.8% males. Knowledge analysis that revealed 63.5% with good understanding, while 23% had good perception towards traffic noise pollution. Chi-square analysis showed that knowledge correlated significantly with age (p=0.010), favoring those over 20 years. Gender did not show a significant impact on knowledge (p=0.453). Perception showed age-related significance (p=0.037) but gender showed no significant influence on perception (p=0.721). Conclusions: The study highlighted positive knowledge levels about traffic noise pollution due to its often-overlooked nature. However, only a small portion exhibited favorable perceptions. This highlights the necessity for focused interventions, especially among the younger generation, to address traffic noise pollution effectively. Consistent education and reinforcement of traffic rules could induce positive change in the health and safety of society.